Legal Protection to Limited Company that Does not Do Adjustments to Business Licensing and Online Single Submission After the Issue of Government Regulation Number 24 of 2018 - Muthia Susan Fadillah Bulolo; Ramlan Ramlan (Randwick International of Social Science Journal, 2021)
Licensing adjustments related to the operational legality of Limited Company that is established before the issued of Government Regulation Number 24 of 2018. For Limited Company (PT) that is established before the issued of Government Regulation Number 24 of 2018 and do not have Master Number Attempted (NIB), but already have Business License Indonesia (SIUP), legally the company can still carry out operational activities. business as usual legally (but imperfectly). This research uses a type of normative research, using a statutory approach and a research approach to the level of vertical synchronization. This research is descriptive analysis, and the results of the study use qualitative analysis. The results show that for legal protection for business actors by adjusting the PT's license to OSS so as not to lose money in order to establish relationships with third parties. Because there are no strict sanctions for business actors who do not make adjustments to PT to OSS.